Uncertainty associated with assessing semen volume: are volumetric and gravimetric methods that different?. (1st October 2016) - Woodward, Bryan; Gossen, Nicole; Meadows, Jessica; Tomlinson, Mathew
Abstract: The World Health Organization laboratory manual for the examination of human semen suggests that an indirect measurement of semen volume by weighing (gravimetric method) is more accurate than a direct measure using a serological pipette. A series of experiments were performed to determine the level of discrepancy between the two methods using pipettes and a balance which had been calibrated to a traceable standard. The median weights of 1.0ml and 5.0ml of semen were 1.03 g (range 1.02–1.05 g) and 5.11 g (range 4.95–5.16 g), respectively, suggesting a density for semen between 1.03g and 1.04 g/ml. When the containers were re-weighed after the removal of 5.0 ml semen using a serological pipette, the mean residual loss was 0.12 ml (120 μl) or 0.12 g (median 100 μl, range 70–300 μl). Direct comparison of the volumetric and gravimetric methods in a total of 40 samples showed a mean difference of 0.25ml (median 0.32 ± 0.67ml) representing an error of 8.5%. Residual semen left in the container by weight was on average 0.11 g (median 0.10 g, range 0.05–0.19 g). Assuming a density of 1 g/ml then the average error between volumetric and gravimetric methods was approximately 8% ( p  < 0.001). If, however, the WHO value for density is assumed (1.04 g/ml) then the difference is reduced to 4.2%. At least 2.4–3.5% of this difference is also explained by the residual semen remaining in the container. This study suggests that by assuming the density of semen as 1 g/ml, there is significant uncertainty associated with the average gravimetric measurement of semen volume. Laboratories may therefore prefer to provide in-house quality assurance data in order to be satisfied that 'estimating' semen volume is 'fit for purpose' as opposed to assuming a lower uncertainty associated with the WHO recommended method.